The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1093/nar/gku729
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the catalytic core of Rad2: insights into the mechanism of substrate binding

Abstract: Rad2/XPG belongs to the flap nuclease family and is responsible for a key step of the eukaryotic nucleotide excision DNA repair (NER) pathway. To elucidate the mechanism of DNA binding by Rad2/XPG, we solved crystal structures of the catalytic core of Rad2 in complex with a substrate. Rad2 utilizes three structural modules for recognition of the double-stranded portion of DNA substrate, particularly a Rad2-specific α-helix for binding the cleaved strand. The protein does not specifically recognize the single-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 56 publications
1
32
0
Order By: Relevance
“…Multiple studies have demonstrated that overexpression of exonuclease 1 ( EXO1 ) rescues the DNA damage sensitivity of rad27Δ mutants [ 56 – 59 ]. Exo1 and Rad27 are both Rad2 family nucleases and crystal structures of their human homologs, FEN1 and EXO1, reveal highly conserved mechanisms of substrate binding and cleavage [ 60 62 ]. Thus, we hypothesized that Exo1, like Rad27, may cleave flaps before RPA can bind to them.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies have demonstrated that overexpression of exonuclease 1 ( EXO1 ) rescues the DNA damage sensitivity of rad27Δ mutants [ 56 – 59 ]. Exo1 and Rad27 are both Rad2 family nucleases and crystal structures of their human homologs, FEN1 and EXO1, reveal highly conserved mechanisms of substrate binding and cleavage [ 60 62 ]. Thus, we hypothesized that Exo1, like Rad27, may cleave flaps before RPA can bind to them.…”
Section: Resultsmentioning
confidence: 99%
“…SAXS data for the RPA DNA binding core bound to 30-nts of ssDNA was used to generate the model for RPA bound to the undamaged strand in the NER bubble 97 . While not incorporated in Figure 8 for clarity, further modeling can incorporate the structure of XPF-ERCC1 in complex with the XPA ERCC1-binding region and the structurally characterized portions of TFIIH and XPG 56-67,98 . XPA interactions with XPC and DDB1-XPE complexes are also relevant to modeling the early stages of assembling the NER incision complex.…”
Section: Xpa Interaction With Other Proteinsmentioning
confidence: 99%
“…The main section of the protein centers around a central seven‐strand mixed β sheet that is flanked on both sides by α helices. The connectivity of helices and sheet is generally very similar to that observed in the FEN1 family members . However, CtGEN1 lacks the helical arch that selects the single‐stranded flap of the DNA substrate in FEN1.…”
Section: The Structure Of Ctgen1mentioning
confidence: 60%